The Influence Of Transformational Leadership And Organizational Innovation On Employee Performance With Creativity As A Mediating Variable - Ria Yuli Hastini; Rr. Erlina; Nova Mardiana (Science and Education Journal (SICEDU), 2026)
Digital transformation requires Civil Servants (CSs) to demonstrate adaptive, The rapid development of digital transformation has required educational institutions to enhance employee performance through effective leadership, organizational innovation, and the development of creativity. This study aims to analyze the influence of transformational leadership and organizational innovation on employee performance, with creativity serving as a mediating variable at Baitul Jannah Islamic School Bandar Lampung. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 125 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that all proposed hypotheses were supported. Transformational leadership has a positive and significant effect on employee performance. Organizational innovation also has a positive and significant effect on employee performance. Furthermore, creativity was found to mediate the relationship between transformational leadership and employee performance, indicating that the implementation of transformational leadership can foster employee creativity and subsequently improve performance. Creativity also mediates the relationship between organizational innovation and employee performance, suggesting that organizational innovation creates conditions that encourage the development of employee creativity and enhance performance. These findings demonstrate that employee performance is influenced not only by transformational leadership and organizational innovation directly but also through creativity, which plays an important role in bridging the relationships between transformational leadership, organizational innovation, and employee performance.